Retrospective Analysis of Gut Microbiota and Metabolomic Profiles in Pregnant Women: Association with Cesarean Section Risk - Yuan J; Wang Y; Liu L (International Journal of Women's Health, 2025)
Jing Yuan,1,* Yabing Wang,2,* Lijuan Liu3 1Anesthesiology and Surgical Department, Zhongshan Campus of the Fourth Hospital of Shijiazhuang, Shijiazhuang, Hebei, 050000, People’s Republic of China; 2Obstetrics Department, Shijiazhuang Fourth Hospital, Shijiazhuang, Hebei, 050000, People’s Republic of China; 3Family Planning Service Center Laboratory, Zhangjiakou Chongli District Maternal and Child Health Care Hospital, Zhangjiakou, Hebei, 075200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Yuan, Email nbi112@126.comBackground: The gut microbiota and metabolic profiles of pregnant women undergo dynamic changes throughout gestation, potentially influencing the mode of delivery. Emerging evidence suggests that dysbiosis of gut microbiota and metabolic perturbations may contribute to the rising cesarean section (CS) rates. This study aimed to investigate gestation-specific alterations in gut microbiota and serum metabolomes and evaluate their association with CS risk.Methods: We conducted a retrospective analysis of 80 healthy pregnant women with singleton pregnancies who delivered at our hospital between January 2022 and December 2023. Participants were stratified into CS (n=40) and vaginal delivery (VD, n=40) groups based on delivery mode, matched for maternal age, pre-pregnancy BMI, and gestational age. Fecal samples were collected one month prior to delivery for gut microbiota analysis using 16S rRNA gene sequencing. Serum samples were subjected to targeted metabolomics via UHPLC-QTOF-MS, focusing on markers of energy metabolism. Peripheral blood was analyzed for T cell subsets and regulatory T cells (Tregs) by flow cytometry. Spearman correlation analysis was performed to assess associations between gut microbial taxa and serum metabolites.Results: The CS group exhibited significantly lower gut microbial α-diversity (Shannon index: 3.22 vs 4.10, P< 0.001), reduced Bacteroidetes (15.3% vs 20.1%, P=0.021), and increased Firmicutes (50.2% vs 46.4%, P=0.015), resulting in an elevated Firmicutes/Bacteroidetes ratio (P=0.008). Metabolomic analysis showed higher levels of pyruvic acid and lactate and lower levels of phenylalanine in the CS group (all P< 0.05). Immune analysis revealed increased CD4⁺ T cells, CD8⁺ T cells, and Tregs in the CS group (P=0.042, 0.029, 0.015, respectively). Correlation analysis indicated that Bacteroidetes abundance positively correlated with lactate (r=0.45, P< 0.001), Firmicutes with phenylalanine (r=0.37, P=0.012), and Lactobacillus negatively with pyruvic acid (r=− 0.28, P=0.045).Conclusion: Gestational gut microbiota dysbiosis and metabolic dysregulation are significantly associated with increased CS risk. These findings highlight potential biomarkers for early risk stratification and suggest that personalized microbiota-directed interventions during pregnancy might help optimize delivery outcomes. Further mechanistic studies are warranted to validate causality.Keywords: pregnant women, gut microbiota, metabolomics, cesarean section, delivery mode, biomarkers